2019
DOI: 10.1111/vru.12797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic differentiation between portal venous and parenchymal gas may be important for the prognosis of canine and feline hepatic emphysema: 37 cases

Abstract: The aim of this retrospective, cross‐sectional, study was to evaluate clinical findings and outcomes for different ultrasonographic patterns of hepatic emphysema in dogs and cats. Dogs and cats with an ultrasonographic diagnosis of hepatic emphysema and a known outcome, from January 2010 to January 2018, were enrolled. The following data were recorded from medical and ultrasonographic records: ultrasonographic patterns of hepatic emphysema (parenchymal, portal venous, biliary), clinical signs, laboratory findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…To date, CT characteristics of HPVG are not described in veterinary medicine, whereas imaging features of PB in small animals are limited to the recognition of some gas within the gallbladder or the biliary tree. 19,22,23 Based on the results of the present study, HPVG and PB showed different CT features in small animals. First of all, the location of the gas was similar to that reported in people: the gas was located in the periphery of the liver (reaching almost the hepatic capsule) in case of portal gas, but had a central location in case of gas in the biliary tree.…”
Section: F I G U R Ementioning
confidence: 51%
See 4 more Smart Citations
“…To date, CT characteristics of HPVG are not described in veterinary medicine, whereas imaging features of PB in small animals are limited to the recognition of some gas within the gallbladder or the biliary tree. 19,22,23 Based on the results of the present study, HPVG and PB showed different CT features in small animals. First of all, the location of the gas was similar to that reported in people: the gas was located in the periphery of the liver (reaching almost the hepatic capsule) in case of portal gas, but had a central location in case of gas in the biliary tree.…”
Section: F I G U R Ementioning
confidence: 51%
“…23,[27][28][29][30] Nevertheless, the MinIP technique was described in human literature for the detection of intrahepatic gas only in postmortem CT. 31 Differentiating between HPVG and PB is important because of their different clinical significance, and because they recognize different causes (leading to different treatments). As already described both in human and veterinary medicine, 3,4,19 PB was commonly associated with biliary surgery (cholecystoduodenostomy), and the presence of gas in the biliary tree is secondary to a connection between the gastrointestinal tract and the biliary tree. Another cause of PB, also in agreement with previous literature, 19,22,23 was emphysematous cholecystitis.…”
Section: F I G U R Ementioning
confidence: 84%
See 3 more Smart Citations